A study to determine the awareness and behavioral patterns/practice about road safety measures among undergraduate medical students, Bangalore, India-cross sectional study - M. S., Ramya; Jadhav, Jyothi; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2017)
Background: Road traffic accident’s (RTA’s) is an important global public health problem causing 20 to 50 million non-fatal injuries and 1.25 million deaths annually, currently the 8th leading cause of death globally and predicted to become the 5th leading cause of death by 2030. RTA is one of the leading cause of death among the most productive age group (15-29 years) costing billions of dollars to deal with its consequences. The present study is aimed to determine the awareness and behavioral patterns about road safety measures among undergraduate medical students, Bangalore. Methods: A cross-sectional study was conducted among 540 undergraduate medical students in a medical college, Bangalore from August to October, 2015 by universal sampling technique using a semi-structured, pre-tested questionnaire. Results: Majority of the study participants were aware of traffic signal rules 99.2% and helmets usage 98.8%. 87.7% knew that alcohol consumption is dangerous while driving/riding, 67% were aware of seat belts usage and only 64.8% were aware of usage of hands free devices while driving/riding. Among the 392 two wheeler and 188 four wheeler users, 36.2% and 50% regularly used helmets/seatbelts respectively and 70% followed lane rule. The risky behaviours like jumping traffic signals, riding hands free, drag racing and drunken driving were noted. Conclusions: In order to restrict the epidemic of RTA’s undertaking proper road safety measures are the best available interventions. The overall knowledge and practice of road safety measures was high except in certain areas the practice levels were not desirable which has to be strengthened.